Gambaran Penggunaan Obat Off-Label Pada Pasien Pediatrik Rawat Inap di Rumah Sakit - Nur Rasdianah; Maimun Datau; Andi Makkulawu; Dizky Ramadani Putri Papeo; Teti Sutriati Tuloli (Indonesian Journal of Pharmaceutical Education, 2022)
Off-label drugs can be interpreted as drugs that are used not in accordance with drug information, distribution permits and sales licenses from the Marketing Authorization (MA) related to indications, age, dosage, route of administration and contraindications. The use of off-label drugs in children occurs because of incomplete data on pharmacokinetics, pharmacodynamics and side effect of a drug. It is because clinical research in children is quite difficult and not in accordance with research ethics and morals, so it has the potential to cause errors in treatment and unwanted drug reactions. This study aims to describe the use of off-label drugs in hospitalized pediatric patients at RSUD of Dr. M.M Dunda Limboto, Gorontalo District, Gorontalo Province. This is an  observational study using cross sectional design and retrospective data collection. The sampling technique applies a purposive sampling technique with a total of 155 patients who meet the inclusion criteria during the January-June 2020 period. The finding shows that from 155 patient medical records, there are 172 (16,51%) off-label drug used with a total of 1042 drugs. The off-label drugs used in the indication category are 64,53%, the off-label drugs used in dose category are 17,44%, the off-label drugs used in age category are 14,53%, the off-label drugs used in route of administration category are 3,49% and the off-label drugs used in contraindications category are not found. The are the most off-label drugs used in each category, including domperidone (off-label in indications and dose), rhinofed (off-label in age) and salbutamol (off-label in route of administration).